(untitled) (Research, Society and Development, 2021)
Objective: to compile data on the social isolation related to the pandemic of COVID-19 as a risk factor for the increase in domestic violence suffered by children and adolescents. Methodology: An integrative literature review was carried out by actively searching the VHL and Pubmed databases, in addition to consulting the WHO, UNESCO, UNICEF and Ministry of Health online pages. As inclusion criteria, articles from the year 2020 were selected, which related social isolation, COVID-19 and domestic violence against children and adolescents. Results: The COVID-19 pandemic can exacerbate or trigger various forms of violence, especially against women and children. There are several reasons that lead to domestic violence, among them are: economic insecurity and stress related to poverty, quarantines and social isolation, reduced availability of access to health services, in addition to the difficulty of assistance for groups at risk. Although domestic violence has increased during this quarantine period, complaints have decreased, especially with regard to children and adolescents, due to the closure of schools and the reduction of the support network formed by relatives and friends of the family. Conclusion: The social isolation caused by the COVID-19 pandemic is a risk factor for the increase in domestic violence against children and adolescents.